Elements of food product safety and its relationship with the concept of preserving life in maqasid shariah - Hashim, Khairul Effendi; Tumiran, Mohd Amzari; Mohammad, Nasharuddin (Penerbit UiTM, 2022)
The safety of food products is an important factor in preserving consumers’ lives. Preserving life is one of the main concepts in achieving the objectives of legal legislation, which is referred to as maqasid shariah. This study focuses on implementing the concept of maqasid shariah, preserving life through the safety of food products to maintain the body and ensure human health, starting from preparing raw materials until the product is ready to eat. This study aims to refine the safety elements of food products and their relationship with the concept of preserving life in the maqasid shariah. Several elements of food product safety were found to be related to the concept of preserving life in the maqasid shariah, namely: (a) material elements in production (buildings and premises, manufacturing and logistics workers, raw materials and ingredients, and equipment and fittings); and (b) elements of the production process (product manufacturing, product packaging, product storage, and product logistics). In conclusion, this study suggests that the concept of preserving life in the maqasid shariah can be applied to the food manufacturing chain process through the food product safety elements identified. A field study approach using primary data as the main data is recommended for future studies to obtain a realistic picture of the implementation of the maqasid shariah in food product safety.